1 12 + 1 13 = 1 · 13 12 · 13 + 1 · 12 13 · 12 = 13 156 + 12 156 = 13 + 12 156 = 25 156 ≈ 0.160
1 12 - 1 13 = 1·13 12·13 - 1·12 13·12 = 13 156 - 12 156 = 13 - 12 156 = 1 156 ≈ 0.006
( 1 10 )3 = 1 1000
( 25 156 )2 = 625 24336
( 1 156 )2 = 1 24336
625 24336 ÷ 1 24336 = 625 24336 × 24336 1 = 625·24336 24336·1 = 15210000 24336 = 625 · 24336 24336 = 625 = 625
625× 1 1000 = 625·1 1000 = 625 1000 = 5 · 125 8 · 125 = 5 8 = 0.625
(х + 7,9) : 2,29 = 10 (х - 56,3) : 37 + 25,9 = 0,13 · 200
х + 7,9 = 10 · 2,29 (х - 56,3) : 37 + 25,9 = 26
х + 7,9 = 22,9 (х - 56,3) : 37 = 26 - 25,9
х = 22,9 - 7,9 (х - 56,3) : 37 = 0,1
х = 15 х - 56,3 = 0,1 · 37
х - 56,3 = 3,7
х = 3,7 + 56,3
х = 60